DIGITAL PRESERVATION OF INTANGIBLE CULTURAL HERITAGE OF JOGET DANCE MOVEMENT USING MOTION CAPTURE TECHNOLOGY - Mohd Firdaus Mohd Herrow; Nur Zaidi Azraai (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
Culture and heritage play a major role in the Malay community in terms of linguistic, art craft, traditional ceremonies, music, activities, and performing arts. The Malay folk dances are most frequently described as a way of human expression through movement and traditional elements in storytelling, ritual, feeling manifestation, and conveying the Malay manner and customs as pillars of the Malay ethnic. Joget was created based on Branyo, a famous Portuguese folk dance. It is a hybrid of culture between the West and the East, reflecting heavily the Malay identity and characteristics as the core philosophy of choreography in the routine. The new creation of Malay dance has positively impacted Malay cultural activities. It has also threatened the original dance form which is being forgotten further from the philosophy. This paper was executed using a qualitative descriptive approach. Interviews and literature reviews were used to expose the rich diversity of two-element; joget and motion capture technology. Data verification, data compilation, data comparison, and triangulation are used as a form of data analysis. The results of the study found that the practice of motion capture has been massively used in digitising intangible assets for 3D application in the form of gaming, video interactive, education entertainment, and learning animation as a platform of education and training as a preservation and protection strategy. But motion capture technology has the potential to be explored as a medium in discovering a quality of trajectory micro visualization of joget dance movement and analyse the symbols or signs that can benefit to the young generation that provides a local sense of unity and belongingness that can help develop a new interest in enhancing cultural values and appreciation.